A Case of Rosai-Dorfman Disease Successfully Treated by Corticotherapy - Alioune Badara Diallo; Moustapha Ndiaye; Moussa Seck; Mohamed Keita; Elimane Seydi Bousso; Sokhna Aissatou Touré; Blaise Félix Faye; Saliou Diop (Case Reports in Hematology)
Rosai-Dorfman disease (RDD) is a benign histiocytic proliferation that results in nodal and extranodal involvements. It is a rare disease, with fewer than 1,000 cases reported in the literature, which explains its lack of knowledge by physicians and the lack of codified therapeutic strategies. We report the case of an 8-year-old girl who presented a rapidly progressive cervical lymph node mass; the diagnosis of RDD was made based on histology and immunohistochemistry. The patient was treated with oral corticosteroids at a dose of 1 mg/kg/d with a favorable outcome and no recurrence after one year of follow-up. This observation illustrates the clinical presentation and diagnosis of this rare clinicopathological entity. The prognosis and treatment options are also discussed.